Publicly available low-cost sensor measurements for PM2.5 exposure modeling: Guidance for monitor deployment and data selection. (January 2022) - Bi, Jianzhao; Carmona, Nancy; Blanco, Magali N.; Gassett, Amanda J.; Seto, Edmund; Szpiro, Adam A.; Larson, Timothy V.; Sampson, Paul D.; Kaufman, Joel D.; Sheppard, Lianne
Highlights: High-resolution PM2.5 models were developed with low-cost PurpleAir measurements. An independent dataset was used to validate model performance at cohort locations. A PCA-based similarity metric was proposed to guide low-cost monitor deployment. Model improvement was observed after incorporating low-cost PurpleAir measurements. PurpleAir monitors with higher PCA similarity resulted in larger model improvement. Abstract: High-resolution, high-quality exposure modeling is critical for assessing the health effects of ambient PM2.5 in epidemiological studies. Using sparse regulatory PM2.5 measurements as principal model inputs may result in two issues in exposure prediction: (1) they may affect the models' accuracy in predicting PM2.5 spatial distribution; (2) the internal validation based on these measurements may not reliably reflect the model performance at locations of interest ( e.g., a cohort's residential locations). In this study, we used the PM2.5 measurements from a publicly available commercial low-cost PM2.5 network, PurpleAir, with an external validation dataset at the residential locations of a representative sample of participants from the Adult Changes in Thought - Air Pollution (ACT-AP) study, to improve the accuracy of exposure prediction at the cohort participant locations. We also proposed a metric based on principal component analysis (PCA) - the PCA distance - to assess the similarity between monitor and cohort locations to guide monitor deployment and data selection. The analysis was based on a spatiotemporal modeling framework with 51 "gold-standard" monitors and 58 PurpleAir monitors for model development, as well as 105 home monitors at the cohort locations for model validation, in the Puget Sound region of Washington State from June 2017 to March 2019. After including calibrated PurpleAir measurements as part of the dependent variable, the external spatiotemporal validation R 2 and root-mean-square error, RMSE, for two-week concentration averages improved from 0.84 and 2.22 μg/m 3 to 0.92 and 1.63 μg/m 3, respectively. The external spatial validation R 2 and RMSE for long-term averages over the modeling period improved from 0.72 and 1.01 μg/m 3 to 0.79 and 0.88 μg/m 3, respectively. The exposure predictions incorporating PurpleAir measurements demonstrated sharper urban-suburban concentration gradients. The PurpleAir monitors with shorter PCA distances improved the model's prediction accuracy more substantially than the monitors with longer PCA distances, supporting the use of this similarity metric.